2005
DOI: 10.1002/pmic.200500001
|View full text |Cite
|
Sign up to set email alerts
|

Surface plasmon resonance imaging-based protein arrays for high-throughput screening of protein-protein interaction inhibitors

Abstract: The E7 protein produced by high-risk human papillomavirus (HPV) induces a degradation of the retinoblastoma tumor suppressor RB through direct interaction, which suggests that an inhibitor for the interaction can be a potential anticancer drug. A surface plasmon resonance (SPR) imaging-based protein array chip was developed for the high-throughput screening of inhibitor molecules targeting RB-E7 interaction. The glutathione S-transferase-fused E7 protein (GST-E7) was first layered onto a glutathionylated gold … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 16 publications
0
41
0
Order By: Relevance
“…ML372 could potentially alter SMN ubiquitination by either hindering activation of ubiquitin and thioester bond formation with the conjugating enzyme, or preventing Mib1-mediated ligation of ubiquitin to SMN. To determine which one of the 3 enzymes in the ubiquitination cascade exhibits affinity for ML372, we measured binding capacity using a modified surface plasmon resonance imaging (SPRi) technique calibrated for small molecules (23). We found that ML372 only displays binding to the E3 ligase Mib1 (Supplemental Table 2).…”
Section: Ml372 Is Brain Penetrant and Has A Reasonable Exposure And Hmentioning
confidence: 99%
“…ML372 could potentially alter SMN ubiquitination by either hindering activation of ubiquitin and thioester bond formation with the conjugating enzyme, or preventing Mib1-mediated ligation of ubiquitin to SMN. To determine which one of the 3 enzymes in the ubiquitination cascade exhibits affinity for ML372, we measured binding capacity using a modified surface plasmon resonance imaging (SPRi) technique calibrated for small molecules (23). We found that ML372 only displays binding to the E3 ligase Mib1 (Supplemental Table 2).…”
Section: Ml372 Is Brain Penetrant and Has A Reasonable Exposure And Hmentioning
confidence: 99%
“…The interaction of human papillomavirus E7 protein and retinoblastoma tumor suppressor protein RB was studied by Jung and co-workers [49]. Fifteen hundred protein spots containing immobilized E7 protein were produced, and an interaction with added RB protein was detected using SPR.…”
Section: Reflectometric Interference Spectroscopy (Rifs)mentioning
confidence: 99%
“…Until recently, the use of SPR for screening applications has been limited by the low throughput offered by existing devises. The recent development of SPR imaging systems makes it possible to perform SPR assays on high-density microarrays [24,25]. However, the high cost and sophistication of these devises will probably restrict the use of SPR for drug discovery purposes.…”
Section: Optical Label-free Assaysmentioning
confidence: 99%
“…cannot be targeted by drug-like small-molecules). While this may indeed apply to many protein interactions, the elucidation of the structure of an increasing number of protein complexes has revealed a *Address correspondence to this author at the CNRS UPS 2682, Station Biologique, Place Georges Teissier, 29680 Roscoff, France; Tel: (33) 2 98 29 23 22; Fax: (33) 2 98 29 25 26; E-mail: colas@sb-roscoff.fr more subtle reality. First, protein-binding interfaces can be dissected in sets of discrete patches, defined by a geometric clustering of atoms involved in the formation of protein complexes.…”
Section: Introductionmentioning
confidence: 99%